Knowledge dissemination and evaluation in a cervical cancer screening implementation program in Nigeria (2007)
Objectives: Our goals were to train health professionals in Nigeria using the text, "Planning and Implementing Cervical Cancer Prevention and Control Programs: A Manual for Managers", and then evaluate the knowledge dissemination process using a pre- and post-test assessment. The manual was developed by the ACCP, WHO, TARC, PATT-T,Engender Health, TI-TPTEGO, and PAT-TO with funding from the Gates Foundation. It is an inclusive guide to implementation and maintenance of screen-and-treat cervical cancer prevention clinics and is ideally suited for programs operating in the developing world. Methods. Training took place at a conference in Ibadan, Nigeria. Participants included teams of physicians, nurses, bioengineers, data managers, and administrators who met in joint and parallel sessions to "train the trainers". This meeting was designed to provide both training and equipment to personnel to be involved in the implementation of a cervical cancer control initiative in Nigeria. A 36 item pre-test was administered prior to a group study sessions. A slide presentation summarized salient points before the post-test was given. The results were entered into an MS Excel spreadsheet for descriptive statistics about (I) the participants, (2) the test, (3) an examination of profession, years of work experience, years of education, and gender as predictors of two outcomes (low pre-test score and large difference between pre- and post-tests) and (4) overall performance on the exam. Results. There were 70 participants and trainers, of which 53 took the exam. Most of the examinees were physicians. Some participants did not fill out the post-test, leaving their tests inevaluable. A closer look at the test revealed eight questions that were confusing and nine that were too easy. All participant subgroups performed better on the post-test than the pre-test; the improvements were statistically significant. While profession impacted the results, profession was not statistically significant. Years of work experience, years of education, and gender did not affect test results. Conclusions. While the study suffers from a small sample size, a few ambiguous questions, and the need for pilot testing the instrument prior to the meeting, the report evaluates the manual very favorably. The authors showed a significant gain in knowledge. The manual gives "the big picture" and does so with clarity. The text and supplementary material outline the work that needs to proceed in an organized program, and the material was easily understandable in Nigeria. Future evaluations could benefit from more participants and varied learning structures.